(untitled) (Texas Journal of Agriculture and Biological Sciences, 2023)
The current study aimed to find the effective role of S. officinale root extract against the hepatotoxicity of Orlistat in male rats. The University of Kirkuk’s College of Science is where the current study was carried out. 24 mature male rats were purchased from an Iraqi care facility and a pharmaceutical research facility in Baghdad. They ranged in age from 12 to 16 weeks, and their average body weight was 175 to 200 g. The animals were kept in sanitary conditions, were clinically healthy, and were housed in metal cages and glass bottles. Throughout the duration of the trial, food and water were freely available. 24 male albino rats were placed into four groups, each with six rats: Negative group: which received orally normal saline (0.5) ml/kg BW. Positive group: which received orally Orlistat 2 ml/kg BW. Extract group: which received orally S. officinale 150mg/kg BW. Treated group: which received orally Orlistat 2 ml/kg and treated by S. officinale 150mg/kg. About the results of Orlistat administration, the liver showed hypertrophy of certain areas of hepatocytes, congestion and hemorrhage noticed in certain places, hepatocyte degeneration was linked with auxes of nuclei, ambiguous nuclei, karyolysis of nuclei, and fibrosis. Aggregation of lymphocytes was evident in some areas and had a nodular appearance. After administration of Orlistat to induced various liesions in liver and treated with S. officinale root extract, The liver’s cross sections revealed a semi-normal structure, a normal central vein, a semi-normal organization of hepatocytes around the vein, and sinusoids with the same width as those in the control group